Small molecule compounds improve the targeted differentiation efficiency of cerebral organoids from pluripotent stem cells - ZHU Wanwan, ZHOU Jinjuan, XIU Jianbo (Jichu yixue yu linchuang, 2024)
Objective To optimize the conditions and improve the efficiency for the differentiation of pluripotent stem cells (PSCs) into cerebral organoids. Methods Based on the induction differentiation system for inducing human embryonic stem cells (hESCs) H9 towards cerebral organoids, a combination of small molecule compounds was added to the developmental stage of neural progenitor cells in the early stage of cerebral organoid differentiation, and the efficiency of neural progenitor cell formation, apoptosis and differentiation into neurons in cerebral organoids in the differentiation stage were observed through morphology, the expression of marker genes was detected by RT-qPCR and the effect of small molecule compound combination on cerebral organoids was comprehensively evaluated. Results At the critical stage of neural progenitor cell development (1 d-14 d) of cerebral organoids, dorsomorphine, A83-01, GSK-3β inhibitor CHIR99021 and SMAD inhibitor SB-431542 were successively added to the medium. It could significantly increase the expression of marker genes in the neural progenitor cell stage, promote the formation of specific neural tube-like structures and reduce apoptosis in the central region of cerebral organoids. Conclusions By using the combination of four small molecule compounds, the formation efficiency in early cerebral organoids can be significantly improved, apoptosis in cerebral organoids can be reduced, neuronal formation can be promoted, and tissue structure heterogeneity in the culture process can be reduced.